2022
DOI: 10.1101/2022.02.17.480902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The virtual aging brain: a model-driven explanation for cognitive decline in older subjects

Abstract: Healthy aging is accompanied by heterogeneous decline of cognitive abilities among individuals, especially during senescence. The mechanisms of this variability are not understood, but have been associated with the reorganization of white matter fiber tracts and the functional co-activations of brain regions. Here, we built a causal inference framework to provide mechanistic insight into the link between structural connectivity and brain function, informed by brain imaging data and network modeling. By applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…The temporal evolution of the brain FC is represented by sliding window technique and it is quantified via switching index (for further detail Material and Methods section). The index related with brain fluidity (Figure 1E) (Hansen et al, 2015; Melozzi et al, 2019; Courtiol et al, 2020) quantifies the switching behaviour of resting state networks (Rabuffo et al, 2021; Lavanga et al, 2022). Empirical resting-state fMRI analysis showed that patients with cognitive decline had a significant reduction in both homotopic dysconnectivity (Figure 2B), and brain fluidity as measured by FCD variance of the limbic network (Figure 2C) (Pillai’s Trace = 0.86, F (4, 218) = 40.97, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal evolution of the brain FC is represented by sliding window technique and it is quantified via switching index (for further detail Material and Methods section). The index related with brain fluidity (Figure 1E) (Hansen et al, 2015; Melozzi et al, 2019; Courtiol et al, 2020) quantifies the switching behaviour of resting state networks (Rabuffo et al, 2021; Lavanga et al, 2022). Empirical resting-state fMRI analysis showed that patients with cognitive decline had a significant reduction in both homotopic dysconnectivity (Figure 2B), and brain fluidity as measured by FCD variance of the limbic network (Figure 2C) (Pillai’s Trace = 0.86, F (4, 218) = 40.97, p < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, reduced inter-hemispheric homotopic FC (Figure 1D) is also associated with AD (Wang et al, 2015, Qiu et al, 2016). Functional connectivity dynamics (FCD) (see Figure 1.E) refers to the flexibility of the brain to flow between different states to facilitate cognition and has been shown to be altered in healthy lifespan (Battaglia et al, 2020, Petkoski et al, 2022), normal mild-life and older adults (Lavanga et al, 2022), and AD (Córdova-Palomera et al, 2017, Jie et al, 2018). These changes in FCD may provide insight into the neural mechanisms underlying cognitive decline in AD.…”
Section: Introductionmentioning
confidence: 99%
“…This is thought to reduce the capacity to also behaviorally switch between concepts and to slow the rate of functional adaptations to external influences (Escrichs et al, 2021 ; Lee et al, 2019 ; Xia et al, 2019 ). Computational models showed that reduced metastability is a response to SC decline (Deco & Kringelbach, 2016 ; Lavanga et al, 2022 ; Naik et al, 2017 ). Hence, the functionally highly interconnected system found in the second component could point towards a low capacity to switch between functional states potentially resulting from the incipient SC decline and would explain the strongest association with cognitive performance decline.…”
Section: Discussionmentioning
confidence: 99%
“…Higher overall communication in the brain, that is, connectivity, requires higher energy consumption (Tomasi et al, 2013 ). At the same time, a highly interconnected functional system reduces the ability to efficiently switch between brain states (Chan et al, 2014 , 2017 ; Colcombe et al, 2005 ; Goh, 2011 ; Nashiro et al, 2017 ; Park et al, 2004 ), which is associated with lower cognitive performance (Lavanga et al, 2022 ). Accordingly, the functional connectivity system of this third component could reflect a rather low‐energy state of the resting brain, which at the same time may involve a high ability to efficiently adapt to external stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation